Predation on turtle nests in the southwestern coast of the Baja California - Lía Méndez-Rodríguez; Ticul Álvarez-Castañeda (Revista Mexicana de Biodiversidad)
The coyote (Canis latrans) is one of the most widely distributed and opportunistic carnivores in North America. It feeds on a variety of differents pecies, ranging from small- (rodents) to medium-sized mammals (Lagomorpha), reptiles, and birds. Among sea turtles, the main species nesting on the coasts of Baja California is Lepidochelys olivacea. Solitary turtles arrive to beaches in low numbers. The aim of this study was to assess the effect of coyote predation on sea turtle nests on pristine beaches of Baja California Sur, Mexico. Of a total of 43 nests observed, 34 (79.1%) were considered as recent, and 9 (20.9%) as old nests; of these, 35 (81.4%) and 8 (18.6%) showed evidence of digging/not digging by predators, respectively. Eggshells were observed around and inside all preyed upon nest holes. Coyotes should be considered an important predator of turtle nests in the Baja California Peninsula.